Integration of taguchi method and digital metrology for precision fused deposition modelling of PLA-based vibration-damping components - Danang Yudistiro; Salahuddin Junus; Dani Hari Tunggal Prasetiyo; Istiqomah Rahmawati; Helda Wika Amini; Meta Fitri Rizkiana (Jurnal Polimesin, 2026)
This study integrates the Taguchi method and 3D digital metrology to improve dimensional accuracy in the Polylactic Acid (PLA)-based Fused Deposition Modelling (FDM) process. The research focuses on the fabrication of vibration-damping roller components in a Continuously Variable Transmission (CVT) system that demands high geometric precision. A Taguchi L9 experimental design was used to analyze the effects of layer height, extrusion temperature, and filling density on the volume deviation of the printed product. The evaluation was conducted using 3D scanning and analyzed using the Signal-to-Noise (S/N) ratio and Analysis of Variance (ANOVA). The optimal parameter combination was obtained at a layer height of 0.25 mm and an extrusion temperature of 220 °C, resulting in the minimum volume deviation and the highest process stability. The ANOVA results identified layer height as the most dominant factor, followed by extrusion temperature, while filling density had a relatively small effect. Validation tests showed good agreement between the predictions and the experimental results. These findings confirm the effectiveness of integrating the Taguchi method with digital metrology in supporting the development of PLA-based precision additive manufacturing for sustainable automotive component applications.This study integrates the Taguchi method and 3D digital metrology to improve dimensional accuracy in the Polylactic Acid (PLA)-based Fused Deposition Modelling (FDM) process. The research focuses on the fabrication of vibration-damping roller components in a Continuously Variable Transmission (CVT) system that demands high geometric precision. A Taguchi L9 experimental design was used to analyze the effects of layer height, extrusion temperature, and filling density on the volume deviation of the printed product. The evaluation was conducted using 3D scanning and analyzed using the Signal-to-Noise (S/N) ratio and Analysis of Variance (ANOVA). The optimal parameter combination was obtained at a layer height of 0.25 mm and an extrusion temperature of 220 °C, resulting in the minimum volume deviation and the highest process stability. The ANOVA results identified layer height as the most dominant factor, followed by extrusion temperature, while filling density had a relatively small effect. Validation tests showed good agreement between the predictions and the experimental results. These findings confirm the effectiveness of integrating the Taguchi method with digital metrology in supporting the development of PLA-based precision additive manufacturing for sustainable automotive component applications.